2020
DOI: 10.1111/jdv.16534
|View full text |Cite
|
Sign up to set email alerts
|

Did Whatsapp® reveal a new cutaneous COVID‐19 manifestation?

Abstract: Figure 2 Chilblain: Source of chilblain posts (a), Post on Facebook (b), Chilblain observed by teledermatology (c) and Chilblain (d).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 8 publications
2
53
0
7
Order By: Relevance
“…real-time reverse transcriptase polymerase chain reaction (rRT-PCR) testing were variable. [1][2][3] Recalcati et al 2 reported 14 cases of patients with skin symptoms consistent with previous described COVID-19 lesions, but all the patients were tested negative. They asked for a serology to validate the hypothesis that these lesions are related to COVID-19.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…real-time reverse transcriptase polymerase chain reaction (rRT-PCR) testing were variable. [1][2][3] Recalcati et al 2 reported 14 cases of patients with skin symptoms consistent with previous described COVID-19 lesions, but all the patients were tested negative. They asked for a serology to validate the hypothesis that these lesions are related to COVID-19.…”
supporting
confidence: 71%
“…Most of dermatological manifestations during the COVID-19 involved the cutaneous microvascular system with acral eruption with possible bullous evolution, chilblain-like lesions, transient livido reticularis and acrocyanosis. [1][2][3]5 Because endothelial cells express ACE2, a receptor for SARS-CoV-2, microvascular lesion is consistent with pathophysiology of COVID-19. While evidence of SARS-CoV-2 in the lung during the acute phase has been provided through electron microscope, immunohistochemical staining and rRT-PCR, only inflammatory lesions were found in other organs and tissues.…”
mentioning
confidence: 80%
“…In a WhatsApp group of French dermatologists, 295 cases with cutaneous manifestations were collected. The most common cutaneous finding was chilblain‐like eruption with 146 posts 19 . Most of the contributors were dermatologists in private practice with milder cases of possible COVID‐19 disease.…”
Section: Chilblain‐like Eruptions On Fingers and Toesmentioning
confidence: 99%
“…None. 1 L. Frumholtz, 3 M. Mrad, 3 A. Petit, 3 E. Zuelgaray, 3 M. Bagot, 3,4 J.D. Bouaziz, 3,4, † T.A.…”
Section: Conflict Of Interestmentioning
confidence: 99%